Labour exploitation in human trafficking law / Amy Weatherburn. - Weatherburn, Amy (Human rights research series, 2021)
The 2000 Protocol to Prevent, Suppress and Punish Trafficking in Persons Especially Women and Children, supplementing the United Nations Convention against Transnational Organized Crime provides the first internationally agreed definition of the human trafficking. However, in failings to clarify the exact scope and meaning of exploitation, it has created an ambiguity as to what constitutes exploitation of labour in criminal law. The international definition's preference for an enumerative approach has been replicated in most regional and domestic legal instruments, making it difficult to draw the line between exploitation in terms of violations of labour rights and extreme forms of exploitation such as those listed in the Protocol. This book addresses this legal gap by seeking to conceptualise labour exploitation in criminal law.